Producing the planar multiphoton sources by photonuclear technique: 1. A model of gamma-fluorescent source - Uvarov, V.L. (Вопросы атомной науки и техники, 2016)
The possibility is shown to produce the planar -sources with the two and more spectral bands in the photon energy range up to ~100 keV by activating K-lines of the characteristic -ray radiation in the thin layers of the elementary substances by an external single-photon -source. A one-dimensional model of a combined planar source in the form of a stack of foils from the inactive and active materials has been developed. The model enables the analysis and optimisation of a source against its intensity and spectral composition. A variant of a production target for manufacturing at an electron accelerator the planar -sources on the basis of the isotopes ⁵⁷Со and ¹⁷⁹Та is offered and investigated by computer simulation. It is shown, that from the viewpoint of yield of the isotopes, suitable for the use in absorptiometry, the photonuclear method is competitive as compared with the reactor and cyclotron technologies.